2016
DOI: 10.1371/journal.pone.0161741
|View full text |Cite
|
Sign up to set email alerts
|

Novel Centromeric Loci of the Wine and Beer Yeast Dekkera bruxellensis CEN1 and CEN2

Abstract: The wine and beer yeast Dekkera bruxellensis thrives in environments that are harsh and limiting, especially in concentrations with low oxygen and high ethanol. Its different strains’ chromosomes greatly vary in number (karyotype). This study isolates two novel centromeric loci (CEN1 and CEN2), which support both the yeast’s autonomous replication and the stable maintenance of plasmids. In the sequenced genome of the D. bruxellensis strain CBS 2499, CEN1 and CEN2 are each present in one copy. They differ from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 70 publications
(96 reference statements)
1
16
0
Order By: Relevance
“…Hybrids are also a widespread state among wine yeast, where natural or laboratory obtained combinations between two species could have interesting technological properties 62 , 66 69 . Other form of genome dynamics was also highlighted for the diploid CBS 2499 strain possessing specific centromeric loci configuration that enables genome rearrangements and ploidy shifts 43 . Based on the body of knowledge concerning other polyploid micro- and macro-organisms and the prevalence of polyploid strains highlighted in this study, we assume that B. bruxellensis has adapted to environmental stress factors by the means of genome plasticity, namely polyploidy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hybrids are also a widespread state among wine yeast, where natural or laboratory obtained combinations between two species could have interesting technological properties 62 , 66 69 . Other form of genome dynamics was also highlighted for the diploid CBS 2499 strain possessing specific centromeric loci configuration that enables genome rearrangements and ploidy shifts 43 . Based on the body of knowledge concerning other polyploid micro- and macro-organisms and the prevalence of polyploid strains highlighted in this study, we assume that B. bruxellensis has adapted to environmental stress factors by the means of genome plasticity, namely polyploidy.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies highlight an important intraspecific diversity of B. bruxellensis 14 , 20 , 38 , 40 which makes the prediction of its occurrence and behaviour in industrial fermentations difficult. Further, recent genetic studies on a limited number of strains 24 , 41 , 42 have suggested that polyploidy and hybridisation may play a significant role in microevolution of the species, along with plasticity in chromosomal structure due to “untraditional” centromeres 43 . The role of polyploidy in adaptive changes to suit environment and/or lifestyle has been observed in other organisms 44 47 , notably for S. cerevisiae which shares similar fermentation niches to those occupied by B. bruxellensis .…”
Section: Introductionmentioning
confidence: 99%
“…Despite the genome of Brettanomyces being highly dynamic and karyotypes strongly variable (Hellborg and Piškur, 2009;Curtin and Pretorius, 2014), we could display an overview of the polymorphic subtelomeric regions where more variation is expected (Brown et al, 2010). The centromeric loci CEN1, CEN2, responsible for chromosome rearrangements and change of ploidy (Ishchuk et al, 2016) is located in scaffold I. Scaffold I also contains a maltose assimilation cluster (MAL31, MAL11, IMA1), similar to the one already described in brewer's yeast in which is essential for maltose degradation (Needleman et al, 1984;Horák, 2013;Needleman and Michels, 2015). In this case, no transcriptional activator such as ScMAL13 is present, but just an α-glucosidase surrounded by maltose permeases and transporters.…”
Section: Chromosomal Organization Of the Reference B Bruxellensis Ummentioning
confidence: 99%
“…Brettanomyces [17,[35][36][37][38][39]. This genome plasticity is thought to be a mechanism in yeast for adaptation…”
Section: Chromosomal Rearrangements and Karyotype And Ploidy Variabimentioning
confidence: 99%
“…Brettanomyces (Landry et al, 2006, Hellborg and Piskur, 2009, Vigentini et al, 2012, Borneman et al, 2014, Ishchuk et al, 2016, Avramova et al, 2018. This genome plasticity is thought to be a mechanism in yeast for adaptation to new environments and niches, and in response to new stressors (see Marsit et al (2017)…”
Section: Extensive Rearrangements Are Present Throughout Brettanomycementioning
confidence: 99%